Implementasi nilai-nilai Pancasila di Pondok Pesantren Tahfidzul Qur`an - Hidayah, Hikmatul (Maliki Interdisciplinary Journal, 2024)
The nation's generation must be able to implement Pancasila values ​​as a guide to life, something that can be done through various methods and institutions, one of which is Islamic boarding schools. This research aims to describe and analyze Islamic boarding school activities by instilling Pancasila values ​​in Islamic boarding school life. Tahfidz al-Qur'an is a process of memorizing to maintain and preserve the purity of the holy book Al-Qur'an. This research aims to explore the problems of learning tahfidz al-Qur'an by proposing solutions to overcome them. And citing what Pancasila values ​​are applied at the Tahfidzul Quran Islamic Boarding School. The data collection technique in this research is by means of observation and documentation. In conclusion, the students of the Tahfidzul Quran Islamic Boarding School instill Pancasila as a source of establishing good relationships with others and forming Al-Quran ethics in their daily lives so that they always protect and preserve the Al-Qur`an